2009
DOI: 10.1583/08-2685.1
|View full text |Cite
|
Sign up to set email alerts
|

Carotid Revascularization Using Endarterectomy or Stenting Systems (CaRESS):4-Year Outcomes

Abstract: ¤ ¤Purpose: To examine the 4-year outcomes from Carotid Revascularization using Endarterectomy or Stenting Systems (CaRESS) in light of the current reimbursement guidelines for carotid artery stenting (CAS) from the Centers for Medicare and Medicaid Services (CMS).Methods: CaRESS was designed as a prospective, nonrandomized comparative cohort study of a broad-risk population of symptomatic and asymptomatic patients with carotid stenosis. In all, 397 patients (247 men; mean age 71 years, range 43-89) were enrol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…38 The results should probably be independent of the use of cerebral protective devices. In our series, the 1-year mortality rate was 2.7%.…”
Section: Figmentioning
confidence: 98%
“…38 The results should probably be independent of the use of cerebral protective devices. In our series, the 1-year mortality rate was 2.7%.…”
Section: Figmentioning
confidence: 98%
“…Operator experience ranged from a minimum of 2 years' experience 25 to 50 CEAs per year with a ,3% stroke or death rate. 27 The demographics of patients in all the trials were similar with an average age of 64-72 years and 65%-70% of participants were male. Medical treatment consisted of aspirin alone in Veterans Affairs; aspirin and discussion of risk factors in Asymptomatic Carotid Atherosclerosis Study (ACAS); aspirin, statins, and antihypertensives to varying degrees in ACST and Carotid Revascularization Endarterectomy versus Stenting Trial (CREST); and was not stated in General Anaesthesia Versus Local Anaesthesia for Carotid Surgery (GALA) and Carotid Revascularization Using Endarterectomy or Stenting Systems (CaRESS).…”
Section: -45mentioning
confidence: 84%
“…Five were randomized controlled trials and the sixth was a high-quality cohort study. 27 The number of endarterectomies ranged from 170 to 1,405 per study. Operator experience ranged from a minimum of 2 years' experience 25 to 50 CEAs per year with a ,3% stroke or death rate.…”
Section: -45mentioning
confidence: 99%
See 1 more Smart Citation
“…3 For this reason, 2,3 the high proportion of ''baseline'' post-CEA restenotic lesions in the CAS arm of CaRESS is likely to have driven (and can explain the finding of) an apparently higher CAS restenosis rate in the overall study population at 4 years (14.7% versus 5.9%, p50.014). 1 The CAVATAS (Carotid and Vertebral Artery Transluminal Angioplasty Study) trial 4 (413 patients with carotid artery stenosis randomized to endovascular treatment or CEA) reported that significant (.70%) restenosis was more common after endovascular treatment than after CEA, both at 1 year (10.5% versus 2.5%, p,0.001) and at 5 years (30.7% versus 10.5%, p,0.0001). In CAVATAS, stenting was performed in only 22% of patients allocated to endovascular treatment, whereas angioplasty alone did not always lead to appropriate dilation of the carotid lesion.…”
mentioning
confidence: 99%